EMPIRICAL OPERATIONALIZATION OF SUCCESSFUL AGING: A SUCCESSFUL AGING INDEX. (16th November 2018) - Ng, K; Tareque, M; Chan, A
Abstract: Previous studies examining successful aging often incorporated arbitrary measures and thresholds to define successful agers, resulted in the prevalence of successful agers ranging from 0.4% to 95%. Longitudinal studies that would enable testing successful aging indexes against mortality are also lacking. We aim to operationalize the construct of successful aging by using empirical approach. First, we construct a list of indicators after reviewing the proposed models. We ran principal component analysis (PCA) on these indicators using data from a nationally representative sample of older Singaporean adults (≥ 60 years old) to determine the factor structure of the indicators. Factor scores were used to construct the successful aging index (SAI). Cox regression modeling was employed to examine the predictive validity of the index scores on mortality. PCA yielded a simple factor structure consisting 6 factors, which explained 51% of the total variance. Notably, the 6 factors extracted were distinct from the widely-proposed 3 factor bio-psycho-social models. Overall, on a scale of 0–100, the Singaporean population had a mean SAI score of 54. For each point increase in SAI score, mortality was reduced by 3.7% on 6-year follow-up (p<0.001, HR=0.963, 95% CI=0.952–0.974), after controlling for covariates. We empirically tested theoretical models of successful aging by PCA. This method enabled us to show pilot data on the factor structure of successful aging indicators, enabling the creation of a SAI. Given the predictive ability of SAI in relation to mortality, enhancing the indicators of SAI may promote successful aging and potentially decrease mortality.